Feasibility Study of a Model that evaluates the Learner Experience: A Quantitative and Qualitative Analysis - Corbari Dos Santos, Gabriela; Dos S. Silva, Deivid Eive; M. C. Valentim, Natasha (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Learner eXperience (LX) is a concept derived from User eXperience (UX) and it can be defined as the perceptions, answers, and performances of learners interacting with learning environments, educational products, and resources. Evaluating the LX to obtain experiences that support and facilitate learning and knowledge mastery is important. Thus, we developed the LEEM to assess and improve the learner’s experience using Digital Communication and Information Technologies during learning. The LEEM is a generic evaluation model and can be used for any level of education; it can be worked independently of the discipline and used with any educational technology. Therefore, this paper presents a feasibility study to evaluate the LEEM steps and sentences from the perspective of potential users. Nineteen teachers from different levels of education participated in this study. The study results were analyzed and generated in a new version of LEEM. The results showed positive points of LEEM, such as a practical, objective, easy-to-use, and useful model. In addition, opportunities for improving some items and sentence of LEEM was obtained. The teachers also suggested adding a description at the ends of the scales to facilitate the response to the items. This study contributes to creating a body of knowledge about LEEM, analyzing its use feasibility and evolution.